Global City Blues - George; Shirley (London : Island Press, 2006)
In Global City Blues, renowned architect Daniel Solomon presents a
perceptive overview and insightful assessment of how the power and
seductiveness of modernist ideals led us astray. As an alternative
Solomon discusses how architecture and cities can offer a vital counterbalance
to the forces of sprawl, urban disintegration, and placelessness
that have so transformed the contemporary landscape.
Keywords: City planning; Urbanization; Modernism